Improve the performance of solar cells using new designs for pelvic center wheel Type V compound mirrors encased by Vernil glasses (Baghdad Science Journal, 2006)
Design and build a center basins new p-type four mirrors were studied its effect on all parameters evaluating the performance of the solar cell silicon in the absence of a cooling system is switched on and noted that the efficiency of the performance Hzzh cell increased from 11.94 to 21 without cooling either with cooling has increased the efficiency of the